2019
DOI: 10.3390/jcm8030341
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biomarker Characteristics According to Clinical Spectrum of Alzheimer’s Disease (AD) in the Validation Cohort of Korean Brain Aging Study for the Early Diagnosis and Prediction of AD

Abstract: We aimed to present the study design of an independent validation cohort from the Korean Brain Aging Study for the Early Diagnosis and Prediction of Alzheimer’s disease (AD) (KBASE-V) and to investigate the baseline characteristics of the participants according to the AD clinical spectrum. We recruited 71 cognitively normal (CN) participants, 96 with subjective cognitive decline (SCD), 72 with mild cognitive impairment (MCI), and 56 with AD dementia (ADD). The participants are followed for three years. The Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 77 publications
(97 reference statements)
4
61
2
Order By: Relevance
“…The observation that approximately one-third of cognitively normal older adults have AD pathology in their brains has been approved by previous amyloid imaging [18][19][20] and neuropathological studies [21,22]. Similar distributions were found in studies of Asian populations [23][24][25]. Therefore, the cutoff values to define abnormal CSF core biomarkers were < 115.1 pg/ml (lower onethird) for Aβ 1-42 , > 40.05 pg/ml (upper one-third) for P-tau, and > 187.32 pg/ml (upper one-third) for T-tau, respectively Aggregated tau and neurodegeneration groups were merged to reduce the number of groups to be compared, which resulted in four different biomarker group combinations, including stage 0, stage 1, stage 2, and suspected non-AD pathology (SNAP).…”
Section: Discussionmentioning
confidence: 52%
“…The observation that approximately one-third of cognitively normal older adults have AD pathology in their brains has been approved by previous amyloid imaging [18][19][20] and neuropathological studies [21,22]. Similar distributions were found in studies of Asian populations [23][24][25]. Therefore, the cutoff values to define abnormal CSF core biomarkers were < 115.1 pg/ml (lower onethird) for Aβ 1-42 , > 40.05 pg/ml (upper one-third) for P-tau, and > 187.32 pg/ml (upper one-third) for T-tau, respectively Aggregated tau and neurodegeneration groups were merged to reduce the number of groups to be compared, which resulted in four different biomarker group combinations, including stage 0, stage 1, stage 2, and suspected non-AD pathology (SNAP).…”
Section: Discussionmentioning
confidence: 52%
“…Rossetti et al [24] described the CERAD total score in AD patients, and the normal control for four years showed a significantly greater decrease in AD patients than in the normal group. Hwang et al [25] confirmed that the CERAD scores decreased as the disease progressed through three years of follow-up of participants in the cognitive normal, SCD, MCI, and ADD groups, and CSF Aβ42 levels in each group also decreased in correlation. In 2019, Meng et al [14] described that an increase in MDS-OAβ levels in AD patients correlated with episodic memory loss.…”
Section: Discussionmentioning
confidence: 88%
“…In 2019, Meng et al [14] described that an increase in MDS-OAβ levels in AD patients correlated with episodic memory loss. Other studies have reported that scores on language-related evaluative tasks such as word list memory and word list recall reflect AD-associated cognitive and memory function changes [25,26]. Furthermore, the decrease in the CERAD score in the order of normal individuals, MCI, and AD correlated with the atrophy of white matter lesions and gray matter in the brain [27], and scores for the word list recall and memory from the CERAD had a close relationship with atrophy in the medial temporal lobe [28].…”
Section: Discussionmentioning
confidence: 99%
“…The ADD patients met the criteria for dementia by the Diagnostic and Statistical Manual of Mental Disorders 4th Edition, Text Revision (DSM-IV-TR) [12] and were diagnosed with probable ADD according to the NIA-AA core clinical criteria [1]. The patients were recruited from 9 referral hospitals in South Korea (175 from Samsung Medical Center, 135 from Validation Cohort of Korean Brain Aging Study for the Early Diagnosis and Prediction of AD (KBASE-V) [13]). All participants underwent neurologic examination, neuropsychological test, and Apolipoprotein E (APOE) genotyping.…”
Section: Participantsmentioning
confidence: 99%